The Louise A. Boyd expedition to East Greenland, 1933 / O.M. Miller, surveyor in charge - Boyd, Louise Arner, 1887-1972 (American Geographical Society of New York, 1933)
Relief shown by contours and spot heights. Includes reliability diagram and source of compilation key. "Amer. Geogr. Soc. special publ. no. 18, Pl. III" -- upper right margin. A) Head of Franze Josef Fiord and vicinity B) Photogrammetrical survey at Blomster Bay, East Greenland c) Trigonometrical control and location of photogrammetrical bases in the survey of Gregory Valley and vicinity D) Photogrammetrical survey of raised delta at Smedal, East Greenland. Color